Enhancing the environmental sustainability and business resilience of mangrove tourism in East Java through innovation design using META (Mangrove ecosystem transformation approach) - Riyanto, Darwin Yuwono; Santoso, Rudi; Wibowo, Januar (Edelweiss Applied Science and Technology, 2024)
East Java's declining mangrove habitats provide serious problems for local companies that rely on mangrove tourism as well as environmental sustainability. The use of the Mangrove Ecosystem Transformation Approach (META), a thorough framework created to combine environmental preservation and commercial adaptation in the mangrove tourist industry, is examined in this study. This study explores how technological innovation may aid in the management of sustainable tourism by combining quantitative, qualitative, and model-building methodologies. The environmental effects of mangrove tourism are assessed, important elements affecting company resilience are looked at, and it is shown how META might enhance both environmental results and operational efficiency. The results show that META might be used as a model for eco-friendly coastal travel, guaranteeing both.